The Challenges and Implications of Post-Concepts Historical Theory: Historiography of Meaning, Method and Manifestation - Danyal Masood (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
This research article is an attempt to investigate the conceptual development in historical theory to understand knowledge production in contemporary culture of concepts. The contested nature of historical theory evolves with different measures to reconstruct different ideas in historical writings and to communicate and brings the process of historical temporalities alongside. This article deals with epistemic challenges and its implication in building historical theory. Postmodern culture encounters objectivity, positivism and modernist representation in historical discourse, which brought contests for meaning, method and manifestation. This article also tried to analyze the challenges and implications of meaning, method and manifestation in building historical theory as framework which consults historians in their possible design and structure about historical representation, and methodology to define how to solve historiographic problems systematically. Historical theory shares boundaries with other disciplines. It clearly presents a transcendental hope for new history which has the capacity to resolve the personal and political existential crisis. This article tried to employ multidisciplinary inquiry, explores multifaced challenges in the post-concepts period.